ChemInform Abstract: Development of Unimolecular Tetrakis(piperidin‐4‐ol) as a Ligand for Suzuki—Miyaura Cross‐Coupling Reactions: Synthesis of Incrustoporin (XIIIf) and Preclamol (VII). Issue 39 (September 2015) - Nallasivam, Jothi L.; Fernandes, Rodney A.
Abstract An intramolecular tetrakis‐4‐hydroxypiperidinol ligand is developed and successfully used to catalyze the Suzuki—Miyaura cross‐coupling reaction of aryl halides and iodo‐lactones to produce a variety of biarlys and heterocyclic analogs.